2020
DOI: 10.1039/d0tb01042a
|View full text |Cite
|
Sign up to set email alerts
|

Self-recovering dual cross-linked hydrogels based on bioorthogonal click chemistry and ionic interactions

Abstract: The biocompatible, injectable and high water-swollen nature of dual cross-linked hydrogels makes them a popular candidate to imitate the extracellular matrix (ECM) for tissue engineering both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…o60 s). 40 This rapid gelation rate facilitates the application of injectable hydrogel formulations to repair tissue defects. Since there is no copper catalyst involved in the reaction, SPAAC effectively avoids cytotoxicity and is suitable for cell encapsulation in the hydrogel.…”
Section: Strain-promoted Azide-alkyne Cycloadditionmentioning
confidence: 99%
See 1 more Smart Citation
“…o60 s). 40 This rapid gelation rate facilitates the application of injectable hydrogel formulations to repair tissue defects. Since there is no copper catalyst involved in the reaction, SPAAC effectively avoids cytotoxicity and is suitable for cell encapsulation in the hydrogel.…”
Section: Strain-promoted Azide-alkyne Cycloadditionmentioning
confidence: 99%
“…<60 s). 40 This rapid gelation rate facilitates the application of injectable hydrogel formulations to repair tissue defects.…”
Section: Click Chemistrymentioning
confidence: 99%
“…91 The slower gelation typically observed with SPAAC can also be addressed by combining SPAAC with faster physical or chemical gelation strategies. For example, Zhan et al demonstrated that dual-cross-linked PEG hydrogels cross-linked with both SPAAC click chemistry and ionic calcium phosphonate bonds could enable gelation times of <1 min coupled with enhanced mechanical strength and retained biocompatibility, 92 while Brown et al combined SPAAC click chemistry with on-demand photo-cross-linking to simulate muscle stiffening with age or disease. 93 However, the drawbacks of both ionic cross-linking and photo-cross-linking are both reintroduced (at least in part) through such approaches.…”
Section: Click Chemistry Hydrogels For Tissue Engineeringmentioning
confidence: 99%
“…[59][60][61][62] However, the definition of bio-orthogonal chemistry has been gradually expanded to include chemical reactions in vitro as applied in the materials science and medical science. [63][64][65] This review focuses on biomolecule-mediated covalent ligation using a variety of so-called Tag/Catcher systems, enzyme-mediated ligation, incorporation of non-standard amino acids and tyrosine-mediated oxidation ligation for bioorthogonal immobilisation.…”
Section: Genetic Amination and Modification For Directed And Multi-po...mentioning
confidence: 99%
“…59–62 However, the definition of bio-orthogonal chemistry has been gradually expanded to include chemical reactions in vitro as applied in the materials science and medical science. 63–65…”
Section: Enzyme Immobilisation Through Genetic Modificationmentioning
confidence: 99%